11. Revisiting early diagnosis in ALS. Issue 3 (March 2016) - Geevasinga, Nimeshan; Menon, Parvathi; Loy, Clement; Yiannikas, Con; Simon, Neil G.; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objectives: The currently utilized diagnostic Awaji criteria in Amyotrophic Lateral Sclerosis (ALS) can result in a diagnostic delay of up to ten months. Subsequently we utilized a three pronged approach, initially an individual patient data (IPD) meta-analysis was undertaken to evaluate the diagnostic utility of the Awaji criteria. We then performed the first prospective multicenter study looking at the current diagnostic criteria. Finally we looked at the addition of a novel Transcranial magnetic stimulation (TMS) technique as an objective biomarker of upper motor neuron dysfunction, to further improve the current criteria. Methods: An IPD meta-analysis was performed after communicating with key researchers and authors who published diagnostic studies looking at the Awaji criteria. In total IPD was available for 1086 individuals across 8 published studies. Statistical modelling was undertaken using SAS (9.3). The first prospective multicenter study looking at the Awaji criteria was undertaken in Sydney, Australia, according to the STARD criteria in 369 patients. Finally, a prospective multicenter study was undertaken looking at the diagnostic utility of Threshold tracking TMS in 333 patients. Results: An IPD meta analysis of 1086 individuals revealed that the current Awaji criteria were more sensitive than the revised El Escorial criteria (rEEC) in all, except one study (7/8 studies). The Awaji criteria were more robust than the rEEC criteria (Sensitivity Awaji 70%, rEEC 45%, P < 0.0001). The Awaji criteria performed better than the rEEC in both bulbar and limb onset disease ( P < 0.0001). In the multicenter prospective study, the Awaji criteria were compared in a cohort of 369 patients. Specificity was 100% across both criteria. Sensitivity was 57% with the Awaji and 39% with the rEEC criteria. Finally in the TMS prospective study, by objectively measuring evidence of UMN dysfunction, an extra 34% of patients could be diagnosed at the first visit. If TMS changes of cortical dysfunction were added to the current Awaji criteria, the sensitivity of the Awaji criteria could be increased to 86%. Furthermore 88% of Awaji 'Possible' patients could be reclassified as 'Probable/Definite'. Conclusion: Whilst an individual patient data meta-analysis revealed a better sensitivity for the Awaji criteria when compared to the older rEEC criteria, there were still a number of patients that could not be classified early. Furthermore all the studies that have looked at the Awaji criteria have been single centre in design, and generally retrospective in nature. The first prospective multicenter study looking at the Awaji criteria, revealed that the sensitivity of the Awaji criteria was lower than expected, most likely related to the inclusion of patients with early onset disease. Finally by utilizing an objective neurophysiological marker of UMN dysfunction, the diagnosis of ALS could be made earlier, when will then hopefully translate into earlier recruitment into clinical trials, ideally within the critical time frame for therapeutic response.